The active mechanical characteristics of arterial smooth muscle during aneurysm remodeling - Qin, Wenqi; Qiao, Dan; Ren, Mingming; Ye, Xiaoqiang; Yu, Guanghao; Chen, Guangxin; Xing, Jian; Ma, Wei; Yu, Miao; Yuan, Xiaohuan; Ouyang, Kunfu; Tan, Wenchang; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAbdominal Aortic Aneurysm (AAA) is a common vascular disease characterized by progressive expansion and remodeling of the aortic wall. However, with the gradual expansion of blood vessels, the walls of blood vessels cannot withstand the tension and rupture, jeopardizing people’s health.MethodsThe aim of the experiment was to establish an abdominal aortic aneurysm model in rats by applying porcine pancreatic elastase externally, to measure the diameter and thickness of blood vessels as well as hemodynamics using animal ultrasound, to measure the active contraction of blood vessels, the rate of contraction, and the contraction stress using vascular mechanics equipment, and to observe the pathological changes in the process of AAA growth using vascular pathological staining.ResultsThis study revealed that with the escalation of the inflammatory response, there is a breakdown of elastic fibers and collagen fibers, leading to a decrease in the active contraction force of the arteries. However, it was observed that by alleviating the inflammation, there was a notable enhancement in the active contraction force of the arteries.Discussion:To describe the development process of AAA from a biomechanical point of view, to reveal the histopathological mechanism, and thus to identify the theoretical basis for clinical treatment.